Metode Penafsiran Narasi Injil Markus - Gozali, Margareth Christian; Bastanta, Dedi; Tambunan, Parsaoran (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
This article focuses on the interpretation of the type of narrative literature (story) which is directed at the interpretation of the narrative in Mark’s Gospel. The theory used set off from The Hermeneutical Spiral book by Grant R. Osborne which combined with another narrative interpretation theory. The Hermeneutic principles in narrative interpretation are as follows: first, structural analysis, that are macro and micro structures. The macro structure examines the narrative text as a whole to find the author's intention as a whole. The micro structure examines the narrative text in detail so that it can divide the story into action units. Second, analysis of narrative style writing. The principle of this interpretation investigates whether there is chiasmus, inclusion (framework techniques), repetition (repetition) and other literary traits. At this step, various information from primary source commentaries are collected to determine whether there is a particular narrative writing style used by the story writer. Third, editorial analysis of a narrative. This principle of interpretation examines the ways in which narrative writers use sources in the writing of each story. Fourth, the exegetical analysis of a narrative. This principle of interpretation deals with the original grammar of the biblical authorship and semantics (word study). Fifth, a theological analysis of a narrative. In principle a narrative is a theology presented in the form of stories. Sixth, contextualization a story. This principle of interpretation means applying lessons from the story to certain concrete situations today.